Abnormal spontaneous brain activity in females with autism spectrum disorders - Xie, Jiapei; Zhang, Weidong; Shen, Yu; Wei, Wei; Bai, Yan; Zhang, Ge; Meng, Nan; Yue, Xipeng; Wang, Xinhui; Zhang, Xianchang; Wang, Meiyun (Frontiers in Neuroscience, 2023)
Objectives: To date, most of studies on autism spectrum disorders (ASD) have focused on samples that were primarily or entirely males and the brain spontaneous activity changes of females remain unclear. The purpose of this study was to explore the changes of brain spontaneous neural activity in ASD females. Methods: In this study, the resting-state functional magnetic resonance imaging (rs-fMRI) of 41 ASD females and 41 typically developing (TD) control were obtained from the ABDIE database. The amplitude of low-frequency fluctuation (ALFF), fractional ALFF (fALFF) and regional homogeneity (ReHo) of the two groups were calculated to detect the regional brain activity. Two independent samples t-test was used to analyze the difference between ASD and TD groups and p < 0.05 was considered significant after false discovery rate (FDR) correction. Pearson correlation analysis was conducted between social responsiveness scale (SRS) scores and local activity of significantly different brain regions. Results: Compared with typically developing (TD) groups, the values of ALFF and ReHo were significantly increased in left superior temporal gyrus (STG), while the values of ReHo were significantly decreased in left superior frontal gyrus (SFG), left middle occipital gyrus(MOG), bilateral superior parietal lobule(SPL), and bilateral precuneus. Correlation analysis showed that the ReHo of right precuneus was positively correlated to SRS total, social communication and autistic mannerisms. Conclusions: The spontaneous activity changes of ASD females involved multiple brain regions and were related to clinical characteristics. Our results may provide some help for further exploring the neurobiological mechanism of ASD females.